Exploring the stigma experienced by people affected by Parkinson’s disease: a systematic review - Sophie Crooks; Gary Mitchell; Lisa Wynne; Gillian Carter (BMC Public Health)
Abstract Background Stigma significantly impacts individuals with Parkinson’s disease (PD) and their caregivers, exacerbating social isolation, psychological distress, and reducing quality of life (QoL). Although considerable research has been conducted on PD’s clinical aspects, the social and emotional challenges, like stigma, remain underexplored. Addressing stigma is crucial for enhancing well-being, fostering inclusivity and improving access to care and support. The review aims to fill this knowledge gap by synthesising existing literature on PD stigma, examining its effects on individuals and families affected, and identifying areas where interventions could reduce stigma’s impact. Methods This systematic review was conducted following Joanna Briggs Institute guidance. Studies were identified through searches in six databases, relevant websites, and reference lists. Covidence was used for duplicate removal, screening, and data extraction. Thematic analysis identified key themes from qualitative data, while narrative synthesis integrated findings from qualitative and quantitative studies. The review protocol was registered on PROSPERO (CRD42023399343). Results This review included 22 studies published between 2002 and 2024, using both qualitative and quantitative methodologies. Five key themes emerged. The first highlighted stereotypes in PD, such as misconceptions about symptoms, age stereotyping, and supernatural beliefs. The second explored drivers and facilitators of stigma, identifying factors like duration since diagnosis, disease severity, lack of public education, and media representation. The third theme revealed stigma’s impact on mental health and well-being, exacerbating feelings of shame, embarrassment, and social isolation. The fourth, responses and consequences of stigma, detailed strategies employed by individuals with PD to manage stigma, including seeking social support and adopting coping mechanisms. The fifth theme, beyond stigma, explored positive aspects of living with PD, highlighting resilience, positive interactions, and advocacy efforts. Conclusion This systematic review underscores the significant impact of stigma on individuals with PD and their caregivers, manifesting as social isolation, diminished QoL, and psychological distress. Key drivers include public misconceptions, cultural biases, and limited awareness and addressing these challenges requires targeted interventions. Recommendations include education to dispel myths, public awareness campaigns and advocacy efforts to reduce stigma, enhance support, and improve QoL.